The effect of tax incentives, trust in tax authorities, tax morale, and tax socialization on individual taxpayer compliance - Meiryani; Warganegara, Dezie Leonarda; Drajat, Rania Salsabila; Lusianah; Salim, Gazali; Purnomo, Agung; Mat Daud, Zaidi (Virtus Interpress, 2023)
This study aims to find out the problems that occur such as micro, small, and medium enterprises (MSME) taxation, trust in the tax authorities, tax morale, and tax socialization on MSME individual taxpayer compliance in the Bandung Regency area since the contribution of tax revenue from the MSME sector is still relatively small. The research method used is quantitative descriptive. The data used in this study were in the form of a questionnaire distributed to individual MSME taxpayers, based on the Slovin formula, to as many as 98 respondents. Data analysis used the partial least square (PLS) analysis technique through SmartPLS software. The results showed that MSME tax incentives had a positive and insignificant effect on MSME individual taxpayer compliance, trust in tax authorities, and tax morale had a positive effect on MSME personal tax compliance, and tax socialization had a positive and insignificant effect on MSME taxpayer compliance. With the results of hypothesis testing, it can be concluded that in the MSME area, Bandung Regency requires tax socialization, especially taxes for taxpayer compliance.